Peculiarities of the poetics of A. V. Amfiteatrov’s «Woeful Notes»: genre correlations and intertextuality - Комаров, Сергій Анатолійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article is dedicated to the investigation of the typical peculiarities of A. V. Amfiteatrov’s «Woeful Notes»: correlations the essays with genres of different layers of literature, systematic use of the references to the characters and motives from other texts, wide quotation, handling of well-known historical facts. On the material of the publicistical essays that compiled the book the author of the article shows how the writer enriches the form of the essays by including genre characteristics of epistolary literature (letter), oratorical prose (agitation speech), journalism (obituary), memoirs (literary portrait), folklore (anecdote).An example of the using of the epistolary genre in the texts of «Woeful Notes» is the essays «The Response to the Reader-Emigrant» and «H. Wells in Petrograd». In them the writer embodies his own observations and reflections on the Bolshevik system in the form of a letter, quotes fragments of letters from other people who personally experienced the cataclysms of the revolutionary years. The essay «Laughing Woe» is a speech written to speak at the gathering of emigrants to help the starving in Russia. A. V. Amfiteatrov freely structures the text of the report, keeping the only normative structural element of the agitation speech – a call to necessary action.The essays «N. S. Gumilyov», «In Memory of Abram Kaufman» combine the features of an obituary (they are dedicated to the people who have recently died; they contain biographical information about them and evaluation of their activity) and a literary portrait (leaning on personal memories the author of the essays offers characteristics of «living temper» of people of art). Also, the writer includes «historical-biographical» and «everyday-life» (folk) anecdotes into some of the texts of «Woeful Notes». They serve as illustrations of miscalculations of Bolsheviks and the people’s attitude towards Soviet authorities.The rich intertextuality of the book serves as a figurative reflecting of anti-Bolshevik pathos, bringing the portrayed situations and characters to a more global historical and cultural levels. Separate attention is payed to the issue of historical (events of the Time of Troubles, the French Revolution, the characters of the dictators, conquerors, supporters of political violence) and biblical (motives of the Book of Revelation, the parable about «the mite of the widow» from the Gospel of Mark) allusions in A. V. Amfiteatrov’s «Woeful Notes».